2020
DOI: 10.1523/jneurosci.3071-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Specific Optogenetic Deep Brain Stimulation of Subthalamic Nucleus Improves Parkinsonian Motor Behaviors

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is an effective therapy for the motor symptoms of Parkinson's disease (PD). However, the neural elements mediating symptom relief are unclear. A previous study concluded that direct optogenetic activation of STN neurons was neither necessary nor sufficient for relief of parkinsonian symptoms. However, the kinetics of the channelrhodopsin-2 (ChR2) used for cell-specific activation are too slow to follow the high rates required for effective DBS, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 57 publications
6
47
0
Order By: Relevance
“…However, these experiments stimulated at 130 Hz, while kinetics of the variants of ChR2 available at the time were not able to follow such high stimulation frequencies (Gunaydin et al, 2010). More recent studies with mutated opsins [i.e., Chronos, which is capable of following frequencies over 100 Hz (Saran et al, 2018)] have suggested that activation of cell bodies at frequencies relevant to DBS may indeed rescue motor deficits in a PD model (Yu et al, 2020). As with DBS, these investigations demonstrate a frequencydependence of optogenetic effects, and have elucidated multiple neural mechanisms driving the therapeutic motor effects of STN-DBS in animal models.…”
Section: Determining the Neural Mechanisms Underlying The Effects Of mentioning
confidence: 92%
“…However, these experiments stimulated at 130 Hz, while kinetics of the variants of ChR2 available at the time were not able to follow such high stimulation frequencies (Gunaydin et al, 2010). More recent studies with mutated opsins [i.e., Chronos, which is capable of following frequencies over 100 Hz (Saran et al, 2018)] have suggested that activation of cell bodies at frequencies relevant to DBS may indeed rescue motor deficits in a PD model (Yu et al, 2020). As with DBS, these investigations demonstrate a frequencydependence of optogenetic effects, and have elucidated multiple neural mechanisms driving the therapeutic motor effects of STN-DBS in animal models.…”
Section: Determining the Neural Mechanisms Underlying The Effects Of mentioning
confidence: 92%
“…Application of optogenetics in rodent parkinsonian models have shown that optogenetic excitation of cortico-subthalamic fibers in the hyperdirect pathway improves motor symptoms while its inhibition worsened them 10,11,20 . Recently, optogenetic STN-DBS verified the contribution of the STN structure in mediating beneficial effects on motor dysfunction 21 . While the use of optogenetics in parkinsonian models have thus begun to answer fundamental questions around STN-DBS mechanisms, the natural role of the STN as a gate in motor control has been poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, amphetamine significantly increased the number of oscillatory cortical narrow (χ 2 (4)=11.70, p=0.0197, Cramér's V=0. 19) and pallidal (χ 2 (4)=38.75, p=7.8e-8, Cramér's V=0.15) units (Fig.S3, post-hoc at Table S5).…”
Section: Up-and Down-modulation Of Dopamine Up-and Down-shifts Beta-fmentioning
confidence: 98%
“…However, there are some differences between human and NHP characteristic beta oscillations. Human beta range spans higher frequencies, and it is common to find beta oscillations in two separate beta ranges, low (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) and high (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), in some but not all patients. Therefore, we defined active beta range (low-beta, high-beta or both) manually for each patient according to their mean nPSD.…”
Section: Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation